Free and glycosidically bound volatile compounds in quince (Cydonia oblonga Mill) from Kashmir, India - Sarver Ahmed Rather; Nazir Ahmad Mir; Peerzada Rashid Hussain; Prashant Suradkar (Food Chemistry Advances, 2024)
The study reports the presence of 87 free and glycosidically bound volatile compounds in two quince fruit cultivars (Round and Oblong). The major free volatile compounds were ethyl acetate,ethyl (E)-2-butenoate, hexyl butanoate, hexyl 2-methylbutanoate, ethyl 3- phenyl propanoate, α-farnesene, hexanal, 1-hexanol, dihydo-beta-ionol and linalool oxide. The major bound volatiles were ethyl acetate, hexyl pentafluoro propanoate, ethyl hexanoate,  γ-elemene, cyclocitral, megastigmatrienone-II and dihydo-beta-ionol. Among all the volatiles, γ-elemene (in glycosidically bound form), cyclocitral, (E)-β-damascenone (in both free and bound form), were found for the first time in quince fruit. Odour activity values (OAVs) of most potent volatiles were calculated for both free and bound volatiles, with 11 compounds having an OAV above 1. Volatiles with higher OAVs in two varieties were β-ionone, (E)-β-damascenone, (Z, E)-α-farnesene, ethyl 2-methyl butanoate and hexanal, with the highest being 425 for (E)-β-damascenone as free form in ‘Round’ variety. In addition, the off-flavours released from quince juice after enzyme treatment or cooking were identified. In particular, megastigmatrienone-II was identified to contribute tobacco flavour. Thus, it can be concluded that variation in free and bound volatiles between the two quince cultivars resulted in the different organoleptic properties, which would assist consumers in selection of the desired quince cultivar.